The Need for Evidential Corroboration for the Reconstruction of Meanings on Dialogues Obtained by Telephonic Interceptions - Vitor de Paula Ramos (Revista Brasileira de Direito Processual Penal)
The present study is aimed to deal with the reconstruction of meanings of intercepted dialogues. Being so, on the first part, it presents concepts of semiotics and epistemology; on the second part, those concepts are applied to a real case. All of that aiming to answer two questions: (i) is the reconstruction of meanings of texts, words or sentences independent of the context of its use? (ii) how is it possible to get to know the context of the communication? The methodology used is the analysis of bibliography on semiotics and epistemology, using a real case as example.